PRACTICE OF BUYING AND BUYING CORN IN JORONG PADANG SIDONDANG KENAGARIAN SITIUNG SITIUNG DISTRICT DHARMASRAYA REGENCY FIQH PERSPECTIVE MUAMALAH - Refiveldi, Ari Efrion; Caniago, Sulastri (JISRAH: Jurnal Integrasi Ilmu Syariah, 2024)
This research aims to find the form of contract between suppliers and farmers. Background: Suppliers reduce the purchase price of corn fruit during harvest. This research method uses field research with purposeful sampling techniques. Blood sources are suppliers and farmers. Based on the results of research conducted by the author, it can be concluded that the contracts that occur between suppliers and farmers are qard contracts and sale and purchase contracts. Qard contracts are loans for seeds and fertilizer from suppliers to farmers. Meanwhile, the sale and purchase agreement is an agreement between the supplier and the farmer regarding the purchase price during harvest. Suppliers reduce prices at harvest time because of the abundance of fruit during harvest. Suppliers reduce prices during harvest, namely, due to simultaneous harvests, lack of interest in the market, and the quality of young corn fruit rotting quickly.